Inflation Volatility, Monetary Policy, and Exchange-Rate Regimes in Central and Eastern Europe: Evidence from Parametric and Nonparametric Analyses. Issue 1 (2nd January 2017) - Hegerty, Scott W.
Abstract : Years after the fall of Communism, countries in Central and Eastern Europe follow a variety of often-changing exchange-rate and inflation targets. How has inflation behaved under such different regimes? This article compares monthly CPI and PPI inflation for six fixed-rate and four floating-rate currencies before estimating structural breaks in each series. It compares whether the mean and variance differ across the breaks in each series, using parametric and nonparametric tests. Granger causality testing is used to examine spillovers between inflation- and exchange-rate volatility. Overall, time-series properties differ across series and regimes, with the Balkans most susceptible to spillovers between exchange-rate and inflation volatility.